(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
A female patient of 25 years of age came to OPD of National Institute of Ayurveda, Jaipur on 22 September, 2020 with chief complaint of delayed menstruation with scanty flow since 4.5 years. Methodology: Detailed history with all necessary clinical, physical examination and laboratory investigations were carried out. No gross physical and chemical abnormality was found. All the laboratory investigations (including USG and hormonal analysis) were found to be normal. So the treatment was planned according to the symptoms. Diagnosis was made on the basis on the basis of presenting complaints was Artava kshaya. Patient was treated with Tilashelukaravi kwatha for 2 consecutive cycles. Patient was kept on follow up for 1 cycle after cessation of Tilashelukaravi kwatha. Result: Patient had got her menstruation regularly with normal duration while taking medicine. Also the amount of flow was also improved and intensity of pain was reduced effectively from moderate to mild. Even after cessation of medicine she got her menstruation in 30 days with normal amount of flow.